Effect of Amino-2-Pyridine Inhibitor on the Rehabilitation of Chloride Contaminated Reinforced Concrete with Bidirectional Electro-migration Method - Rajput, Tarun Singh (My University, 2023)
The corrosion of reinforcement presents a significant durability challenge, leading to a reduced design life of reinforced concrete structures. With the growing demand for longer service lives of infrastructure (typically 100–120 years) and the high costs involved in construction and maintenance, the repair and rehabilitation of concrete structures have become of utmost importance. To address this issue, a novel method known as Bidirectional Electro-Migration Rehabilitation (BIEM) technology has been developed to enhance the durability of existing reinforced concrete structures. The BIEM process involves applying an electric field between embedded steel cathodes and external anodes to inject a corrosion inhibitor from external electrolytes into the concrete while simultaneously extracting chloride ions from the concrete cover zone. As observed from the literature review in most of the research studies TETA was used as inhibitor so in this thesis the effectiveness of 2AP was studied, effect of Amino-2-Pyridine Inhibitor on the Rehabilitation of Chloride Contaminated Reinforced Concrete with Bidirectional Electromigration method. The effectiveness of the BIEM repair technique was investigated on different aspects as current density, duration of treatment, initial chloride content and variation of inhibitor in the electrolyte. In experimental studies, specimens were treated using the BIEM method, and then drilled to analyse the concentration profiles of corrosion inhibitor and chloride within the concrete. Along with it Icorr, Ecorr, HCP and LPR of the specimens was also monitored and investigated along with chloride and inhibitor profiles. The optimum results was found in the case of 15 of test duration, 1 A current density at 0.3 M inhibitor concentration. The maximum migration of inhibitor was observed 9.16 mM and maximum extraction of chloride ions was 47%. Overall, the BIEM technology shows promise in improving the durability and extending the service life of existing reinforced concrete structures, making it a potential solution for addressing the challenges of concrete corrosion and enhancing the sustainability of infrastructure
Keywords: Bidirectional Electromigration; Concrete; Corrosion; Repair; Inhibitor